Description of Starch Granules From Edible Acorns (Oak), Palms, and Cycads in Southern China - Li, Zhao; Barton, Huw; Wang, Weiwei; Yang, Xiaoyan (Frontiers in Earth Science, 2022)
A review of ethnological and archaeobotanical evidence shows the potential for a range of starch-rich woody plants, beyond tuberous plants, to have been important foods in prehistoric south subtropical China. In this paper we review the size and shape characteristics of starch granules non-tuberous woody plants (Palms, Cycads and Acorns) that our research has identified as important sources of carbohydrates for prehistoric communities. The study sample consists of 34 modern starch reference samples across eight genera (Palms: Arenga, Caryota,; Cycads:Cycas; and, Acorns: Castanopsis, Fagus, Lithocarpus, Quercus, and Quercus section Cyclobalanopsis ). Our descriptive criteria are developed granule descriptors standard in the literature and then assessed for their utility using multiple correspondence analysis. The results demonstrate that both morphometric characteristics and the maximum size of granules are valuable for distinguishing starch granules at various taxonomic levels. Of the five morphometric characteristics recorded in this study sample, granule shape is the most effective variable for granule identification.